Behavioral Analysis and Internal Stress Evaluation of Glue-Laminated Bamboo Space Truss Utilising Carbon Fiber-Reinforced Composite Joints - G. Lucena, Joe Robert Paul; Dela Cruz, Orlean G. (International Journal of Integrated Engineering, 2025)
Truss is a structure composed of straight members forming triangular panels. Truss typically assumes a rigid configuration with connections treated as flexible joints. A commonly used material for truss construction is A36 steel, but due to its lack of sustainability, engineers and architects are increasingly exploring alternatives. Bamboo, traditionally employed in construction, has gained attention for its impressive mechanical properties, positioning it as a viable substitute for steel. This research emphasizes the utilization of "Glubam," a glue-laminated bamboo, as a component in space trusses. The modular tetrahedral space truss is constructed using six Glubam members connected by carbon fiber-reinforced composite joints. The primary objective of this study is to assess the truss prototype’s behavior under various loading magnitudes through practical experimentation. The researcher treated bamboo culms with a boric salt solution, stripped them, and glued them together to form the truss member. Space truss joints were created using a 3D printer. The prototype underwent axial loading ranging from 0 to 490 N at its apex. Stresses, strains, and deformations were measured using LiDARs and strain gauges in an instrumentation setup. The findings suggest that the connectors exhibit elasticity before the Glubam reaches its proportional limit stress of 59 MPa. Experimantation produced nodal displacement-load curves displaying significant linearity, indicating elastic behavior in connectors and members, where stress corresponds to strain. This underscores the promising potential of Glubam and fiber-reinforced composites as materials for truss components.